The Effect of Acuyoga on Fetal Heart among Pregnant Women with Hypertension - Hindun Mila Hudzaifah; Melyana Nurul Widyawati; Ta’adi Ta’adi (International Journal of Nursing and Health Services (IJNHS), 2020)
Acuyoga is a non-pharmacological therapy that has the benefit of accelerating blood circulation to the fetus. The study aimed to examine the effect of Acuyoga to fetal heart rate among pregnant women with hypertension. We conduct a quasi-experimental, pretest and posttest with control group design. Thirty total was allocated in the experimental and control groups. Each group consisted of 15 respondents. Patients in the experimental group received the Acuyoga postpartum awhile control group received the prenatal yoga. the intervention was carried out twice a week for four weeks with a duration of sixty minutes. The results of the dependent statistical test showed an average Fetal Heart Rate test before intervention in the experimental group of 133.47x/minute and after the intervention was given to 146.27 x/minute increasing of 12.8 x/minute. Independent t-test results obtained p-value 0.015 (<0.050). The size of the Cohen d effect is 0.94, which means that acuyoga is very effective in reducing fetal heart rate. Acuyoga for twice a week for four weeks with a duration of sixty minutes was effective to increase fetal heart rate in pregnant women with hypertension